2001
DOI: 10.1248/bpb.24.1338
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Constituents in the Plants 7. Leaves of Clerodendron bungei and Leaves and Bark of C. trichotomum.

Abstract: The constituents of the leaves of Clerodendron bungei STEUD. (Verbenaceae) and leaves and bark of C. trichotomum THUNB. were investigated guided by the antiproliferative activity against three tumor cell lines (MK-1: human gastric adenocarcinoma, HeLa: human uterus carcinoma, and B16F10: murine melanoma). Two phenylethanoid glycoside caffeic acid esters, acteoside and isoacteoside, were isolated as the constituents which selectively inhibit the growth of B16F10 cells.The antiproliferative activities against B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…When we compared the activities of 3Ј,4Ј-di-OH-flavones [luteolin, 6-hydroxyluteolin, eupafolin (11), and cirsiliol (8)], the influence of 5-OH-6,7-di-OCH 3 appears slightly greater, but that of 5,7-di-OH, 5,6,7-tri-OH, and 5,7-di-OH-6-OCH 3 are almost the same. However, the order is 5,7-di-OHϾ5,7-di-OH-6-OCH 3 for apigenin (10) vs. hispidulin (9), 5,7-di-OH-6-OCH 3 Ͼ5-OH-6,7-di-OCH 3 for desmethoxycentaureidin vs. eupatorin (2), and 5,6-di-OH-7-OCH 3 · 5-OH-6,7-di-OCH 3 for 5 vs. 3. Values are means of four determinations.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…When we compared the activities of 3Ј,4Ј-di-OH-flavones [luteolin, 6-hydroxyluteolin, eupafolin (11), and cirsiliol (8)], the influence of 5-OH-6,7-di-OCH 3 appears slightly greater, but that of 5,7-di-OH, 5,6,7-tri-OH, and 5,7-di-OH-6-OCH 3 are almost the same. However, the order is 5,7-di-OHϾ5,7-di-OH-6-OCH 3 for apigenin (10) vs. hispidulin (9), 5,7-di-OH-6-OCH 3 Ͼ5-OH-6,7-di-OCH 3 for desmethoxycentaureidin vs. eupatorin (2), and 5,6-di-OH-7-OCH 3 · 5-OH-6,7-di-OCH 3 for 5 vs. 3. Values are means of four determinations.…”
Section: Resultsmentioning
confidence: 96%
“…Reagents for culture of the tumor cells and for the bioassay were described in a previous paper. 10) The instruments used in this study were a Shimadzu Double Beam Spectrometer UV-200S (UV spectra), JEOL JNM A-500 Spectrometer ( 1 H-NMR and 13 C-NMR spectra), JEOL JMS HX-110 Mass Spectrometer (MS spectra), and Yanaco Micro Melting Point Apparatus (mp).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result has already been reported against rat hepatoma (dRLh-84) cells by Inoue et al 12) We have also observed the phenomenon that the antiproliferative activity of caffeic acid is lowered by esterification. 1) In spite of structural differences, 5 and 3 showed similar activity. Since the activity of catechin was less potent than that of 3 (not shown), the presence of the galloyl group would be a key factor for antiproliferative activity.…”
Section: )mentioning
confidence: 96%
“…13) Furthermore, anti-oxidant activity 14,15) of SR is regarded as a potential cure for hepatitis, inflammation and other chronic diseases. Therefore, acteoside with potent antioxidant properties could offer important biological functions of SR.…”
Section: Identification Of Acteosidementioning
confidence: 99%